Computers in Psychiatry - Lauritsen, Peter Lauritsen; Elsass, Peter (Outlines. Critical Practice Studies, 2001)
Within psychiatric research, the field of ’technotherapy’ has been centred primarily on attempts to assess the computer as a treatment tool. The situation of daily clinical usage is, however, often ignored within such research, as for instance in controlled clinical trials. Our empirical study illustrates how health professionals and clients use different concepts of science and health in the attempts of formulating standards for using computers in psychiatric practice. The psychiatrists at a major psychiatric hospital decided and justified clients’ use of computers on the basis of a ’techno-medical’ quality assurance. At the same hospital the occupational therapists stressed the improvement of social relations as a treatment goal. And, at a psychiatric outside clinic the clients used concepts of ’normality’ for articulating quality in computer use. Our study exemplifies how the use of computers is a multifaceted ’performance’. What is called for is a kind of research not limited by artificial borders of ’the context’ and the ’user-perspective’. In much humanistic research as well as in action research concepts of ’context’ and ’user-perspective’ imply a somehow romantic view on practice as pure and uncontaminated by the outside world contrasted to a ’general’ or an ’objective’ way of knowing the world. These sharp distinctions were however difficult to maintain in our study, where health professionals and clients took local contingencies into account when they interpreted computer use, while they simultaneously drew on a socio-historical reservoir of resources.